2023
DOI: 10.2320/matertrans.mt-mf2022005
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Effect of Grain Size on Mechanical Properties of Magnesium and Its Alloys

Abstract: Recent studies show significant advances in improving the mechanical properties of magnesium and its alloys. While many papers deal with different alloy compositions, it is apparent that grain size plays a key role in the mechanical behavior of these materials. The ability to produce samples with very fine grain sizes leads to observations of high strength and/or high elongations. There are recent reports of exceptional elongations of over 100% in pure magnesium and a few alloys. These recent findings are crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 400 publications
1
7
0
Order By: Relevance
“…The effect of grain size on the mechanical properties of magnesium and its alloys has been recently reviewed, and some trends were revealed [ 44 ]. Experimental data on flow stress and elongation from over 300 papers were collected and then plotted as a function of the grain size.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of grain size on the mechanical properties of magnesium and its alloys has been recently reviewed, and some trends were revealed [ 44 ]. Experimental data on flow stress and elongation from over 300 papers were collected and then plotted as a function of the grain size.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The experimental data of flow stress of magnesium alloys were also plotted as a function of the elongation in tension to evaluate the strength–ductility relationship [ 44 ]. It was reported that grain refinement improves the mechanical properties of magnesium alloys, leading to a significant expansion of range in flow stress, σ, vs elongation plots.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations